2014
DOI: 10.1007/s10461-014-0750-y
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Microbicide Gel Use with Real-Time Notification of the Container’s Opening Events: Results of the CAPRISA Wisebag Study

Abstract: Accurate estimation of the effectiveness of a microbicide for HIV prevention requires valid measurement of adherence to product use. A microbicide gel applicator container (Wisebag), fitted with cell phone technology to transmit opening events and text message reminders, was developed to monitor each opening event of the container as a proxy for gel use and adherence. Ten women were enrolled in a pilot study and followed for up to 4 months. Wisebag opening (WBO) dates and times were recorded and correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Medication regimen adherence was the intervention outcome for 52 of these studies, non-medication treatment adherence was the intervention outcome for 24, and vaccination adherence was the intervention outcome for 21. Medical compliance reminders were found to improve (e.g., taking medication at a scheduled time, completing non-medication follow-up treatment, completing a vaccination regimen) when using an SMS-reminder intervention in 85% (83/97) of studies ( Akhu-Zaheya and Shiyab, 2017 ; Anthony et al, 2015 ; Armstrong et al, 2009 ; Arora et al, 2012 ; Baker et al, 2015 ; Balato et al, 2013 ; Bangure et al, 2015 ; Berenson et al, 2016 ; Chow et al, 2015 ; Chung et al, 2015 ; Cocosila et al, 2009 ; da Costa et al, 2012 ; Davey et al, 2016 ; Dick et al, 2011 ; Downing et al, 2013 ; Dowshen et al, 2013 ; Fang and Deng, 2017 ; Ferguson et al, 2015 ; Foreman et al, 2012 ; Franklin et al, 2006 ; Garofalo et al, 2016 ; Gengiah et al, 2014 ; Georgette et al, 2017 ; Granholm et al, 2012 ; Gu et al, 2016 ; Guy et al, 2013 ; Haji et al, 2016 ; Hanauer et al, 2009 ; Hardy et al, 2011 ; Hirst et al, 2017 ; Hofstetter et al, 2015a ; Hofstetter et al, 2015b ; Huang et al, 2017 ; Huang et al, 2013 ; Johnson et al, 2016 ; Jordan et al, 2015 ; Kamal et al, 2015 ; Keränen and Liikkanen, 2013 ; Khorshid et al, 2014 ; Kollmann et al, 2007 ; Lewis et al, 2013 ; Ludlow et al, 2009 ; Lv et al, 2012 ; Maduka and Tobin-West, 2013 ; Mao et al, 2008 ; Matheson et al, 2014 ; Miloh et al, 2009 ; Miloh et al, 2017 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medication regimen adherence was the intervention outcome for 52 of these studies, non-medication treatment adherence was the intervention outcome for 24, and vaccination adherence was the intervention outcome for 21. Medical compliance reminders were found to improve (e.g., taking medication at a scheduled time, completing non-medication follow-up treatment, completing a vaccination regimen) when using an SMS-reminder intervention in 85% (83/97) of studies ( Akhu-Zaheya and Shiyab, 2017 ; Anthony et al, 2015 ; Armstrong et al, 2009 ; Arora et al, 2012 ; Baker et al, 2015 ; Balato et al, 2013 ; Bangure et al, 2015 ; Berenson et al, 2016 ; Chow et al, 2015 ; Chung et al, 2015 ; Cocosila et al, 2009 ; da Costa et al, 2012 ; Davey et al, 2016 ; Dick et al, 2011 ; Downing et al, 2013 ; Dowshen et al, 2013 ; Fang and Deng, 2017 ; Ferguson et al, 2015 ; Foreman et al, 2012 ; Franklin et al, 2006 ; Garofalo et al, 2016 ; Gengiah et al, 2014 ; Georgette et al, 2017 ; Granholm et al, 2012 ; Gu et al, 2016 ; Guy et al, 2013 ; Haji et al, 2016 ; Hanauer et al, 2009 ; Hardy et al, 2011 ; Hirst et al, 2017 ; Hofstetter et al, 2015a ; Hofstetter et al, 2015b ; Huang et al, 2017 ; Huang et al, 2013 ; Johnson et al, 2016 ; Jordan et al, 2015 ; Kamal et al, 2015 ; Keränen and Liikkanen, 2013 ; Khorshid et al, 2014 ; Kollmann et al, 2007 ; Lewis et al, 2013 ; Ludlow et al, 2009 ; Lv et al, 2012 ; Maduka and Tobin-West, 2013 ; Mao et al, 2008 ; Matheson et al, 2014 ; Miloh et al, 2009 ; Miloh et al, 2017 ...…”
Section: Resultsmentioning
confidence: 99%
“…Two studies did not find that SMS reminder helped increase rate of Hepatitis B and anti-retroviral therapy (ART) medication adherence and, in fact, displayed lower rates of adherence than no reminder or treatment as usual (respectively) ( Linnemayr et al, 2017 ; McIver et al, 2016 ). Lastly, all studies that included a measure of feasibility and/or acceptability found positive results (e.g., Garofalo et al, 2016 ; Gengiah et al, 2014 ; Park et al, 2014 ), even if the intervention was not found to be statistically significant (e.g., Buis et al, 2017 ; Richman et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…These adherence data can be monitored in real-time through standard cellular and internet connections, where the data is secure through an encrypted system and available for future use. Other forms of RTAM devices include blister pack holders and larger devices where vaginal microbicides and/or larger quantities of drug supply can be stored[95]. The main advantage that RTAM has over traditional EAMs is that it provides dose-to-dose adherence data that can lead to an intervention at the precise time when it is most likely to be effective (i.e., when non-adherence has been identified), which usually precedes (and could prevent) viral rebound[94, 96].…”
Section: Measures Of Adherence That Can Lead To Actionable Interventionsmentioning
confidence: 99%
“…There has been considerable attention given to the development of biomarkers and biometric measures that rely less on verbal self-report by participants and provide more direct measures of events or adherence. Examples include electronic devices such as MemsCap and WisePill devices for pill storage and Wisebag for microbicide applicator storage, which allow electronic tracking of when the storage devices are opened, ostensibly for use (or, in the case of rings, for storage) of the product [ 44 , 45 ]. Some biometric approaches may indicate a point-in-time when the product is used, while other approaches may indicate more cumulative use patterns.…”
Section: Discussionmentioning
confidence: 99%